Pendapatan Orang Tua Terhadap Prestasi Akademik Mahasiswa Sastra Arab Universitas Al-Azhar Indonesia - Zaqiatul Mardiah; Yogo Purwono (Universitas Al Azhar Indonesia, 2013)
Abstraksi - Penelitian ini secara umum bertujuan memperoleh fakta empiris tentang pendapatan keluarga dan kaitannya dengan prestasi akademik mahasiswa, khususnya pada mahasiswa sastra Arab UAI. Prestasi akademik merujuk pada indeks prestasi kumulatif per semester atau pertahun. Secara teoritis prestasi akademik dipandang sebagai output dari koleksi investasi dalam pendidikan. Namun, Meskipun prestasi akademik siswa dianggap sebagai output langsung dari input alokasi investasi dalam pendidikan yang diusahakan oleh orang tua, tingkat keberhasilannya dianggap bergantung pada sejumlah faktor eksogen yang melekat pada siswa, keluarga, atau sekolah. Faktor-faktor eksogen ini antara lain adalah kumpulan karakteristik anak atau siswa, seperti jenis kelamin, usia dan kemampuan bawaan. Dengan menggunakan analisa deskriptif dan analisa inference, diperoleh hasil penelitian yang menyatakan bahwa prestasi akademik mahasiswa menurut kelompok pendapatan orang tua, tidak bisa terlihat secara nyata, pada masing-masing tahun masuk atau angkatan di UAI. Hal yang sama juga ditemukan pada analisa perbedaan prestasi akademik mahasiswa menurut kelompok pendapatan orang tua, pada masing-masing kelompok jenis kelamin, status beasiswa, dan pendidikan terakhir sebelum memasuki UAI. Ini menunjukkan bahwa karakteristik siswa belum cukup kuat untuk mendukung kita membedakan perbedaan prestasi akademik mahasiswa berdasarkan pendapatan orang tua mereka. Abstract - The aim of this reseach is to empirically investigate the relation between academic achievement and parent’s income of students in the department of arabic at the University of Al-Azhar Indonesia. The arabic department students that has been admitted to the University from 2008 to 2011 academic year are selected to be a sample in this study. Using the student’s first year grade point average (GPA), as the proxy of student’s academic achievement, and his/her ordinal scaled monthly parent’s income as independent variable, as well as other student’s characteristic variables as additional exogenous variables, the study reveals that the arabic students academic achievement are on average not signficantly different based on their parent’s income, especially for those students with motnhly parents equals to or gretaer than ten million rupiahs (high income level). For those wiht parents income less than ten million rupiahs, there is slightly the negative relation between students academic achievement and their parents income, but the result of testing hypothesis do not support this descriptive statistics. Similar results are found when student’s chracteristics such as gender, admission year into the University, and the type of pre-university eduacation, are included in the analysis. There is no significantly differences in general in academic achievement between students in different parents income level. However if we group students based on their characteristics, there are some differences significantly found in the academic achievement of students in different particular characteristic, especially in different entry academic year, gender or the type of their last education.